Osteomyelitis Risk Factors Related to Combat Trauma Open Upper Extremity Fractures: A Case–Control Analysis. Issue 12 (December 2019) - Warkentien, Tyler E.; Lewandowski, Louis R.; Potter, Benjamin K.; Petfield, Joseph L.; Stinner, Daniel J.; Krauss, Margot; Murray, Clinton K.; Tribble, David R.
Abstract : Objective: To determine risk factors for osteomyelitis in US military personnel with combat-related, extremity long bone (humerus, radius, and ulna) open fractures. Design: Retrospective observational case–control study. Setting: US military regional hospital in Germany and tertiary care military hospitals in the United States (2003–2009). Patients/Participants: Sixty-four patients with open upper extremity fractures who met diagnostic osteomyelitis criteria (medical record review verification) were classified as cases. Ninety-six patients with open upper extremity fractures who did not meet osteomyelitis diagnostic criteria were included as controls. Intervention: Not applicable. Main Outcome Measurements: Multivariable odds ratios (ORs; 95% confidence interval [CI]). Results: Among patients with surgical implants, osteomyelitis cases had longer time to definitive orthopaedic surgery compared with controls (median: 26 vs. 11 days; P < 0.001); however, there was no significant difference with timing of radiographic union. Being injured between 2003 and 2006, use of antibiotic beads, Gustilo–Anderson [GA] fracture classification (highest with GA-IIIb: [OR: 22.20; CI: 3.60–136.95]), and Orthopaedic Trauma Association Open Fracture Classification skin variable (highest with extensive degloving [OR: 15.61; CI: 3.25–74.86]) were independently associated with osteomyelitis risk. Initial stabilization occurring outside of the combat zone was associated with reduced risk of osteomyelitis. Conclusions: Open upper extremity fractures with severe soft-tissue damage have the highest risk of developing osteomyelitis. The associations with injuries sustained 2003–2006 and location of initial stabilization are likely from evolving trauma system recommendations and practice patterns during the timeframe. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.